Issues of Legal Regulation of the Executive Authority in the Republic of Kazakhstan and Foreign Countries - KOZHAKHMETOV, Galym; KUANALEEVA, Guldana; NURZHAN, Saulen (Journal of Advanced Research in Law and Economics, 2017)
This article consecrates topical issues of executive power, which points to one of the most acute problems of world society. The executive branch is recognized as one of the three branches of the unified state power by the current constitutional doctrine and practice of the Republic of Kazakhstan - a unitary state with a presidential form of government. The process of management constant development has a direct impact on the system of executive power and the structure of individual executive bodies, generates the demand for an in-depth analysis of this influence, its consideration in the creation and functioning of an integral, rational, effective state mechanism. In order to create a modern complex theoretical vision for the scientific legal foundations of a strong and effective executive branch operating in the public system of the Republic of Kazakhstan, which is established as a democratic, legal, social and secular state, the highest value of which is a human, his rights and freedoms, in this study are considered the theoretical concepts, practical aspects of the concept and executive power place as a full-fledged element of the state - the object of the constitutional, administrative and legal sanctions; system, structure, legal and organizational forms of executive bodiesactivity; as well as the main problems of legislative regulation, further construction and functioning of the executive power in Kazakhstan.Recommendations and proposals have been developed to improve a number of legal measures for the executive power enhancement. The analysis of the main historical studies that explain the nature of executive power in foreign countries and in Kazakhstan and its main role in the development of the state and law is carried out.